PERLINDUNGAN HUKUM TRANSAKSI JUAL BELI HANDPHONE BEKAS BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Fransiska, Fitri; Heriyanti, Yuli; Sutrisno, Hafiz (Jurnal Pahlawan, 2025)
Abstract The development of information and communication technology has increased public demand for mobile phones, while also giving rise to a market for used phones as a more affordable alternative. However, transactions involving the sale and purchase of used mobile phones often create legal issues related to product condition, clarity of information, warranties, and business actors’ responsibility for consumer losses. Every citizen has the right to fair legal protection and certainty; therefore, consumers must be safeguarded from fraudulent and non-transparent business practices. This study aims to analyze consumer legal protection in used mobile phone transactions based on Law Number 8 of 1999 concerning Consumer Protection. The research employs normative legal methods with statutory and conceptual approaches. The findings indicate that the legal framework is adequate; however, violations still occur, highlighting the need to enhance legal awareness among business actors and consumers and to optimize the role of the Consumer Dispute Settlement Agency. . Keywords : Buying and Selling, Used Mobile Phones, Consumer Protection.